PENDELEGASIAN PENGATURAN OLEH UNDANG-UNDANG KEPADA PERATURAN YANG LEBIH RENDAH DAN AKIBAT HUKUMNYA - Sukardi Sukardi; Ekawestri Prajwalita Widiati (Yuridika, 2010)
Act is an essential instrument in the rule of law. As the basic for governmental regulation, the accuracy and legality of its drafting process should be placed as the main concern. This article examines such models of delegated legislation. In severe legislation product, some problems regarding the mistaken in the delegation process was still founded. This article recommends the importancy of limiting substance for each level of regulation to avoid redundancy. Regulation synchronization is needed in order to avoid inefficiency and reach the maximum aim of what the regulations is made for.